Sifat Rheology dan Sifat Mekanis Beton Semi Ringan Batu Apung dengan Penggantian Sebagian Semen dengan Abu Sekam Padi - Merdana, I Nyoman; Mahmud, Fathmah; Muttakin, Yasid Bastomi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
From point view of earthquake engineering, the greater the mass of a structure, the greater the shear force imposed on the structures, and vice versa. To obtain a lightweight strong structure, lightweight concrete can be used instead of conventional concrete. Lightweight concrete can be made from various types of coarse aggregates, such as pumice. Smooth cracks occurred on the concrete surface due to hydration can be prevented by reducing cement content. Some amount of the cement can be replaced with natural pozzolanic which relatively easy and low-cost to produce. This research is to examine rheological and Mechanical properties of semi light-weight concrete due to partial replacement of cement content with Rice husk ash. The rice husk ash was prepared by burning Rice Husks in a furnace at a temperature of 700°±50°C for 4-hours. The chemical properties of both the Rice Husk Ash and Pumice was also tested in laboratory. In this study, the Compressive strength f’c and the Modulus of Elasticity of concrete Ec were tested with 15x30cm cylindrical specimens prepared according to SNI-1974-2011 tested at age of 28, 56 and 90 days. Based on a series of tests conducted, it was found that the Rheological properties of Semi-Light Pumice Concrete was greatly governed by the Rice Husk Ash. Furthermore, Partial cement replacement with Rice Husk Ash was potentially to be used with an optimum of 5% cement content. The compressive strength and Modulus of Elasticity of Semi Lightweight concrete are influenced by the age of the concrete testing.